Predictive factors of late cholangitis in patients undergoing pancreaticoduodenectomy - Ito, Yasuhiro (World J Surg Oncol, 2018)
BACKGROUND: Because the survival rate for patients experiencing late complications after pancreaticoduodenectomy (PD) is increasing, late complications should receive as much attention as early complications do. METHODS: Between April 2007 and August 2016, 133 patients underwent PD at our institution. We analyzed their cases to determine the predictors of late cholangitis after PD. RESULTS: Of the 133 patients, 28 (21.1%) were diagnosed with postoperative cholangitis. A multivariate analysis showed that abnormal postoperative values of alkaline phosphatase were independently associated with postoperative cholangitis (odds ratio, 3.81; 95% confidence interval, 1.519–9.553; P = 0.004). The optimal cut-off value for postoperative alkaline phosphatase calculated from the receiver operating characteristic curve was 410 IU/L (sensitivity, 76.2%; specificity, 67.9%; area under the curve, 0.73). A univariate analysis to identify risk factors showed that pneumobilia was significantly related to a postoperative alkaline phosphatase value ≥ 410 IU/L (P = 0.041). CONCLUSION: This study suggests that an alkaline phosphatase level ≥ 410 IU/L is a predictor of late postoperative cholangitis. In addition, pneumobilia is also related to the postoperative alkaline phosphatase level. Therefore, alkaline phosphatase levels should be carefully monitored in patients with postoperative pneumobilia in the late postoperative course.